"Aren't They Supposed to Be Healthy?": A Qualitative Exploration of Healthcare Providers on Adolescent Health Services in Malaysia. Issue 3 (3rd July 2022) - Awang, Hafizuddin; Ab Rahman, Azriani; Sukeri, Surianti; Hashim, Noran; Nik Abdul Rashid, Nik Rubiah
Abstract: Adolescent health services are often misperceived as less important scope of health services, hence, diminishing the rights of adolescents to have optimal healthcare services. Inputs on perceptions regarding adolescent health services would facilitate policy makers in improving the quality of healthcare services delivery to adolescent clients attending health facilities. This qualitative study aimed to explore the perceptions of healthcare providers regarding adolescents and adolescent health services in Malaysian setting through in-depth interview. A descriptive, phenomenological approach was employed as the method of inquiry. Thematic analysis was used to evaluate the data. From this study, respondents perceived adolescents as healthy, thus, less important compared to other group of population. Adolescent health services were perceived as a demanding scope of health service; requiring considerable time and specialized clinic settings. Healthcare providers also believed that adolescent health services are crucial yet overlooked, with various management issues such as short-staffed, lack of promotion, budget, and monitoring which hamper its progress. In conclusion, healthcare providers in this study have some negative perceptions toward adolescents and their health services. Improving clinics work processes and setting, allocating more staff and training sessions, gaining more political will and strengthening adolescent-friendly health services are recommended to improve healthcare providers' perceptions toward adolescent health services.